Définir la vie spirituelle des élèves hors des institutions religieuses : un enjeu du Service d'animation spirituelle et d'engagement communautaire (Québec) - Jacques Cherblanc; Marie-Anne Risdon
In 2000, Quebec deconfessionalized its school's system. At the same time, it asked the schools to "facilitate the spiritual development of student" (LIP, art 36). To support this new responsibility, the profession of the spiritual care and guidance and community involvement service (SCGCIS) was created. But, contributing to the spiritual life of students in respect of their freedom of conscience and religion independently of their beliefs is quite a challenge for this new service. After an overview of the historical context and issues raised by various studies and surveys on this subject, we are exploring the results of two research that defined the concept of "spiritual life" conducted with SCGCIS. This brings to light that a phenomenological approach allows to intervene on spiritual life independently of the beliefs or religions. It also helps distinguish between "spiritual life" and "spirituality".